Evaluative Review of Government Obligations in Protecting the Right to Work for Persons with Disabilities through National and Regional Regulations (Ambon City) After the Ratification of the Convention on the Rights of Persons with Disabilities - Siska Giofana Mapusa (Balobe Law Journal, 2021)
Introductioan: Indonesia is a country that upholds the protection of human rights . One of the human rights pillars of concern for Indonesia is legal protection for Persons with Disabilities.Purposes of the Research: The study aims to determine whether the national regulations in Indonesia have accommodated the implementation of the Right to Work in accordance with Article 27 of the Convention on the Rights of Persons with Disabilities (CRPD) and the availability of regulation at the regional level, especially in Ambon as a form of protection for the Disability Right to Work.Methods of the Research: This research was conducted using normative methods. The results of this study were presented in a descriptive analysis report.Results of the Research: The results showed that the Act and regulations in Indonesia have not been maximal in providing protection for workers with disabilities because not all rights in Article 27 of the CRPD were regulated in national regulations. Relating to the protection of the right to work for persons with disabilities in the city of Ambon, there was no district regulations.